Trends in lung cancer screening in the United States, 2016–2017 - Okereke, Ikenna C.; Nishi, Shawn; Zhou, Jie; Goodwin, James S. (Journal of Thoracic Disease; Vol 11, No 3 (March 29, 2019): Journal of Thoracic Disease, 2019)
Background: Lung cancer is the most common cancer killer annually, yet the overall rate of eligible patients who undergo screening with low-dose computed tomography (LDCT) is low. Our goal was to determine factors which were associated with the probability of obtaining lung cancer screening. Methods: The Clinformatics Data Mart (CDM) database, a national commercial health insurance database with over 18,000,000 enrollees, was queried to determine the rate of LDCT screening and factors which influenced receiving LDCT screening. All enrollees between the ages of 55 and 77 from 2016 to 2017 were included. Demographics, history of tobacco exposure and state smoking statistics were recorded. Results: All 8,350,197 enrollees aged 55–77 were included in the study. Among enrollees, the rate of screening increased throughout 2016 and early 2017 and then appeared to stabilize. In the second half of 2017 the LDCT rate was approximately 6 per 1,000 enrollees per year, and was increasing at a slope of 0.1 additional LDCT per 1,000 enrollees per year. There was marked geographic variation, with 5-fold differences in LDCT rates between different regions. There was no correlation between smoking rate and LDCT rate at the state level (r=0.02; P=0.87). Enrollees aged 65–69 were most likely to be screened (OR =1.53; 1.45–1.61) compared to enrollees aged 55–59. Conclusions: The rate of LDCT screening is increasing very slowly with time, and most eligible patients are not screened. Further studies are needed to determine the reasons for low screening rates, and the marked geographic variation.